Analysis of the structure and degree of crystallisation of 70Li2S–30P2S5 glass ceramic. Issue 6 (19th December 2014) - Seino, Yoshikatsu; Nakagawa, Masaru; Senga, Minoru; Higuchi, Hiroyuki; Takada, Kazunori; Sasaki, Takayoshi
Abstract : Structural analysis of 70Li2 S–30P2 S5 glass ceramic by 31 P MAS NMR revealed a strong correlation between the degree of crystallisation and the lithium ionic conductivity. Abstract : Heat treatment of Li2 S–P2 S5 glasses to transform the glass to a glass ceramic enhances the ionic conductivity by precipitating a Li7 P3 S11 metastable crystalline phase with high ionic conductivity. Although the precipitated phase is identical, the conductivity achieved varies depending on the heat treatment conditions. Solid-state 31 P MAS NMR spectroscopy to investigate the structure of the glass ceramic in this study revealed a strong correlation between the ionic conductivity and the degree of crystallisation, in which the conductivity of the glass ceramic increased with increasing proportion of metastable Li7 P3 S11 phase.